Biosorption of copper, chromium and zinc from textile wastewater using euchema spinosum (red alga) - Nur Liyana, Abu Hassan (2019)
Due to the rapid growth of economy in this era many industries were build up in providing the community with supply and need. Water became the most crucial thing since every development is using water as the main source even for the textile industry. However, the abundant of waste water produce during the manufacturing has cause the risk toward human and other living things. As water treatment need the production of chemical in solving waste water issue, this research has come out to use the cost effective and widely available macro alga in aquatic system as biosorbent in removing heavy metals from the real waste water. This research was intended to minimize the use of chemical in water treatment which using the natural macro alga as biosorbent through simple method that is adsorption method. Macro alga is a biological material that has a potential to accumulate the heavy metals onto the surface of the macro alga. This biosorption process can reduce the amount of heavy metals inside the waste water without any harm to human and environment. Macro alga is a non-toxic biomass that provide nutrients and other beneficiaries to the food industry. In this research, a sample of red alga and a sample of textile effluents was chose to study the effectiveness of red alga as biosorbent in removing heavy metals from waste water. The sample of red macro alga known as Euchema Spinosum was collected from Kunak, Sabah while the sample of textile waste water was collected from Tenun Diraja Pahang located at Kuantan, Pahang. An optimum dosage and contact time were identified during the research to investigate the maximum adsorption of copper, chromium and zinc. The selected dosages used in the experiment are 0.25 g, 0.5 g, 0.75 g, 1.0 g, 1.25 g and 1.5 g. After that, the selected contact times for the experiment chose are 1 h, 8 h, 16 h, 24 h, 32 h, 40 h, 48 h, 52 h and 58 h. The laboratory equipment used to measure the heavy metals content is UV-VIS Spectrophotometer. A dilution factor of 50 ml of distilled water is used to dilute the sample of textile waste water due to the thickness of color came from dye used in manufacturing of the textiles. The UV-VIS Spectrophotometer cannot measure over range value of heavy metals if the content of heavy metals is too high. Dilution of sample is necessary in this experiment to accommodate the laboratory equipment. Next, the percentage removal of every heavy metals were calculated. The results and discussions was examined and recorded. The optimum dosage for these three heavy metals is 20 g/L. The optimum contact time found for Copper removal is 24 hours while the optimum contact time for Chromium and Zinc is 40 hours. The highest adsorption capacity of Chromium, Zinc and Copper is 92.67%, 90% and 76% each. Besides, the initial content of Copper shows the highest value followed by Chromium and Zinc. After that, Copper was the least heavy metal uptake capacity for the biosorption compare to Chromium and Zinc. In conclusion, Euchema Spinosum is found very effective in removing Chromium and Zinc but less effective in removing Copper from the textile waste water.